Anti-inflammatory and antibacterial activities of Batuan (Garcinia binucao) fruits - Albano, Zella Faye M.
In this study, fresh fruits of batuan (Garcinia binucao) was evaluated for its antiflammatory and antibacterial activities., The anti-inflammatory assay using Carrageenan-Induced Paw Edema Method showed that n-hexane extracts (65.79 percent) and dichloromethane extracts (64.91 percent) exhibited anti-inflammatory activities comparable to Indomethacin, the positive control (67.11 percent)., The antibacterial assay using Paper Disk Diffusion Method showed that crude methanolic extracts and dichloromethane extracts at 1000ug/mL were most effective against Staphylococcus aureus. The microbial indexes were 0.39, 0.47 and 0.50 respectively. The positive control, Amoxicillin has a 3.39 microbial index. The components of the three most active extracts (crude methanolic, n-hexane and DCM extracts) from both assays were separated through Thi Layer Chromatography and subjected to phytochemical tests. Crude methanolic extracts contain alkaloids, phenolic compounds and cardiac glucosides. Both n-hexane and DCM extracts contained terpenes, alkaloids, saponins, phenolic compounds and cardiac glycosides. These bioactive compounds present may have been responsible for the anti-inflammatory and antibacterial activities of the extracts